Peran Kepolisian Sektor (Polsek) Dalam Menanggulangi Peredaran Dan Penyalahgunaan Narkoba di Kecamatan Simpang Kanan Kabupaten Rokan Hilir - Ayu Lia Lestari; Mimin Sundari Nasution (Lembaga Pengkajian Dan Pengembangan Sumberdaya Pembangunan (lppsp), 2023)
Simpang Kanan District is an area located in Rokan Hilir Regency. Since 2018 Simpang Kanan District has experienced an increase in drug circulation and abuse. So it requires the role of the police in tackling the distribution and abuse of narcotics. The purpose of this study was to determine the role of the police in tackling the distribution and abuse of narcotics in Simpang Kanan District. This study uses a qualitative descriptive research method. With data collection techniques used are primary data and secondary data obtained from observation, interviews, documentation. The results of this study indicate that the role played by the Simpang Kanan Police is inregulatory role Simpang Kanan Police carry out activities based on RI Law Number 8 of 1981 concerning the Criminal Procedure Code, then in enabling role In accordance with the regulations, the Simpang Kanan Police has two programs, namely preventive (prevention) the activities carried out are investigations to investigations and arrests and repression (law enforcement) activities carried out are filing, hereinafter in direct provision of goods and service Supervision activities carried out by the Simpang Kanan Police are checking urine, carrying out Friday vents, conducting socialization or counseling and conducting patrols. In carrying out its role the Simpang Kanan Police have several obstacles, namely from the police themselves who do not understand SOP investigations and from people who do not understand the impact of drugs themselves.